Blizzard of the Blue Moon. - Osborne, Mary Pope; Murdocca, Sal, ill. (New York : Random House, 2006)
The magic tree house carries Jack and Annie to New York City in 1938 on a mission to rescue the last unicorn.
K-3
Keywords: Time travel - fiction; Magic -fiction; Unicorns - fiction; Depressions - 1929 - fiction; Tree houses - fiction; Brothers and sisters - fiction; New York (N.Y.) - History - 1898 - 1951 - fiction